Digital finance and equitable industrial carbon emissions: an empirical analysis of Chinese cities - Heyu Lu; Zongfa Wu (Humanities & Social Sciences Communications)
Abstract Digital finance (DF) serves a pivotal role in facilitating the transition to green economies. While existing literature has explored the impact of DF on carbon emission reduction, the aspect of equity in carbon emissions has been largely neglected. Using a panel dataset of Chinese cities from 2011 to 2020, this study calculates the equitable industrial carbon emission (EICE) for 276 cities in China and quantitatively studies the effect of DF on EICE. The results indicate that DF significantly enhances EICE, with this effect being more pronounced in eastern regions and those with higher levels of internet development. Analysis of the mechanisms shows that DF achieves EICE through four pathways: industrial structure transformation, technological innovation acceleration, energy consumption reduction, and marketisation advancement. Additionally, this study confirms the positive moderating role of governmental environmental concern in strengthening the impact of DF on EICE, though the moderating effect of public environmental concern is not evident. This research provides new insights into evaluating the environmental benefits of the digital transformation of finance and the attainment of EICE.